FT-NIR, MicroNIR and LED-MicroNIR for detection of adulteration in palm oil via PLS and LDA - Basri K.N.; Laili A.R.; Tuhaime N.A.; Hussain M.N.; Bakar J.; Sharif Z.; Zoolfakar A.S.; Mohd Fared Abdul Khir (Royal Society of Chemistry, 2024)
Indexed by WOS/Scopus/ERA